Time Series Forecasting for Clients Rates in Tele-Communication Data using Statistical Techniques - Alhagree, Salah; Alqasemi, Fahd; Alnedami, Ibrahim; Al-Dilami, Redwan (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper applies statistical time-series techniques to forecast clients' rates in telecommunication data. The study focuses on analyzing historical telecommunications data and generating forecasts that can support decision-making and performance analysis in telecom environments.